THE PANCASILA INDUSTRIAL RELATIONS (THE INDUSTRIAL RELATIONS BASED ON THE INDONESIAN FIVE PRINCIPLES – A PHILOSOPHICAL APPROACH) - Soeganda Priyatna (Sosiohumaniora, 2003)
The Method of the Industrial Relations of every country is different, depending on the influence of the country's principle and philosophy. Therefore, Indonesian Industrial Relations is the reflection of the Indonesian way of life, the Pancasila, means five principles, belief in god, humanity, nationalism, democracy and prosperity. The Pancasila Industrial Relation connects itself to the political system as well as to the national method of the Indonesian people and as a result the aims to be achieved will make similar to the nation's great aim. Beside the five principles, the Pancasila Industrial Relations also contain the Trio Duty ( Tridharma ) which carries three elements that develop into a dynamic relation between an employer and a businessman. The Trio Duty consist of : a. Rumongso handarbeni. The principle of partnership consists of two aspects; namely, partners in production and partners in profit. b. Melu hangrungkebi, the principle of partnership in responsibility . c. Mulat sariro hangrosowani, the principle of self-recognition and instropection. The principles stated above can be achieved through a kind of accomodation within the three elements in the Industrial Relations, namely, the workers, businessmen and, the Government. Keyworlds : industrial relations, pancasila, trio duty, partnership, self recognition, introspection.